AN ANALYSIS OF THE INFLUENCE OF PHYSICAL ACTIVITY, GADGET USE, AND DIETARY HABITS ON OBESITY AMONG CHILDREN AGED 9–12 YEARS - Putri Safina, Nursyifa; Fatmawati, Lilis; Alfianti, Khalifatus Zuhriyah (jfpublisher, 2025)
Introduction. Obesity is a condition marked by excessive fat accumulation that threatens health. In Indonesia, obesity among children aged 9–12 years is becoming a significant public health concern. Contributing factors include lack of physical activity, excessive gadget use, and poor dietary habits. Obese children are at higher risk of chronic diseases such as type 2 diabetes, hypertension, and mental health issues. Lifestyle changes and limited awareness about balanced activities, screen time, and nutrition further exacerbate the problem. This study aims to examine the influence of physical activity, gadget use, and dietary patterns on obesity among school-aged children. Method. A quantitative, cross-sectional approach was used with a sample of 37 obese students aged 9–12 years, selected through total sampling. Data were collected using standardized instruments: PAQ-C for physical activity, SAS for gadget use, and a dietary pattern questionnaire. Data analysis employed multiple linear regression. Result&Analysis. The results showed that physical activity, gadget use, and dietary patterns each had a significant effect on obesity (p < 0.05). Low physical activity and high gadget use were associated with higher obesity levels, while healthy dietary patterns had a protective effect. Gadget use was the most dominant factor. Discussion. The study confirms that lifestyle factors significantly contribute to childhood obesity. Excessive gadget use, in particular, reduces physical activity and increases obesity risk. Preventive efforts involving parents, schools, and health professionals are crucial to fostering healthy habits in children.